De la mort à la fabrique du saint dans l’Éthiopie médiévale et moderne - Claire Bosc-Tiessé; Marie-Laure Derat (Afriques)
The episodes surrounding the death of a saint are described that mark stages in recognizing sainthood and establishing a place of worship and pilgrimage. Hagiographic accounts are the main sources of information for the medieval and modern periods about the stakes in each of the episodes described; they also establish de facto a model for the making of a saint. In the effort to describe this model and understand deviations from it, we notice an evolution in saint worship between ancient times and the contemporary period.